The Effect of Omega-3 Fatty Acids on Sarcopenia: Mechanism of Action and Potential Efficacy - Atiporn Therdyothin; Nacharin Phiphopthatsanee; Masoud Isanejad (Marine Drugs, 2023)
Sarcopenia, a progressive disease characterized by a decline in muscle strength, quality, and mass, affects aging population worldwide, leading to increased morbidity and mortality. Besides resistance exercise, various nutritional strategies, including omega-3 polyunsaturated fatty acid (n-3 PUFA) supplementation, have been sought to prevent this condition. This narrative review summarizes the current evidence on the effect and mechanism of n-3 PUFA on musculoskeletal health. Despite conflicting evidence, n-3 PUFA is suggested to benefit muscle mass and volume, with more evident effects with higher supplementation dose (>2 g/day). n-3 PUFA supplementation likely improves handgrip and quadriceps strength in the elderly. Improved muscle functions, measured by walking speed and time-up-to-go test, are also observed, especially with longer duration of supplementation (>6 months), although the changes are small and unlikely to be clinically meaningful. Lastly, n-3 PUFA supplementation may positively affect muscle protein synthesis response to anabolic stimuli, alleviating age-related anabolic resistance. Proposed mechanisms by which n-3 PUFA supplementation improves muscle health include 1. anti-inflammatory properties, 2. augmented expression of mechanistic target of rapamycin complex 1 (mTORC1) pathway, 3. decreased intracellular protein breakdown, 4. improved mitochondrial biogenesis and function, 5. enhanced amino acid transport, and 6. modulation of neuromuscular junction activity. In conclusion, n-3 PUFAs likely improve musculoskeletal health related to sarcopenia, with suggestive effect on muscle mass, strength, physical performance, and muscle protein synthesis. However, the interpretation of the findings is limited by the small number of participants, heterogeneity of supplementation regimens, and different measuring protocols.